هيئات الأمم المتحدة الاشرافية المشاءة بموجب المواثيق الدولية لحقوق الانسان العام 1966 - خضير, وجدان رحم; فضائلي, مصطفى (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This body is considered a relatively recent institution, established in 2006 to assume all duties and responsibilities previously assigned to the Human Rights Commission. It is tasked with improving and streamlining its functions to strengthen the system of special procedures, provide expert oversee complaint mechanisms and provide expert advice. As for the Human Rights Committee, it was established later pursuant to Article 28 of the International Covenant on Civil and Political Rights, by a resolution of the Economic and Social Council on 16 February 1946, and its formation was completed on 21 June of the same year.